2017
DOI: 10.1016/j.euroneuro.2017.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Extrastriatal dopamine D2-receptor availability in social anxiety disorder

Abstract: Alterations in the dopamine system are hypothesized to influence the expression of social anxiety disorder (SAD) symptoms. However, molecular imaging studies comparing dopamine function between patients and control subjects have yielded conflicting results. Importantly, while all previous investigations focused on the striatum, findings from activation and blood flow studies indicate that prefrontal and limbic brain regions have a central role in the pathophysiology. The objective of this study was to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 53 publications
(67 reference statements)
0
21
0
Order By: Relevance
“…In a PET study using another D 2 /D 3 receptor ligand, 11 C-(S)-(2)-5-bromo-N-((1-ethyl-2-pyrrolidinyl)methyl)-2,3-dimethoxybenzamide ( 11 C-FLB 457), researchers confined their analysis to extrastriatal regions and reported increased D 2 /D 3 binding in SAD in orbitofrontal cortex and dorsolateral prefrontal cortex (Fig. 3) (33). A study that used 123 I-iodobenzamide SPECT to investigate dopaminergic function in SAD patients with comorbid obsessive-compulsive disorder reported dopaminergic deficits in patients with comorbidity, whereas those with obsessive-compulsive disorder alone demonstrated no differences from the healthy control group (34).…”
Section: Research Into Functional Neurochemistrymentioning
confidence: 99%
“…In a PET study using another D 2 /D 3 receptor ligand, 11 C-(S)-(2)-5-bromo-N-((1-ethyl-2-pyrrolidinyl)methyl)-2,3-dimethoxybenzamide ( 11 C-FLB 457), researchers confined their analysis to extrastriatal regions and reported increased D 2 /D 3 binding in SAD in orbitofrontal cortex and dorsolateral prefrontal cortex (Fig. 3) (33). A study that used 123 I-iodobenzamide SPECT to investigate dopaminergic function in SAD patients with comorbid obsessive-compulsive disorder reported dopaminergic deficits in patients with comorbidity, whereas those with obsessive-compulsive disorder alone demonstrated no differences from the healthy control group (34).…”
Section: Research Into Functional Neurochemistrymentioning
confidence: 99%
“…Cortical functions of Drd2 are of interest, considering the involvement of dopamine transmission in the regulation of behavioral dimensions including fear, anxiety, cognition, attention, working memory and information processing in schizophrenia and mood disorders (Seamans JK and CR Yang 2004;Durstewitz D and JK Seamans 2008;Cervenka S et al 2012;Brisch R et al 2014;Tovote P et al 2015;Wang Y et al 2016;Plavén-Sigray P et al 2017). A majority of studies have focused on the role of Drd2 in prefrontal cortex pyramidal neurons and interneurons, particularly the parvalbumin (PV) subtype because of their potential contribution to cognitive dysfunctions in schizophrenia (Seamans JK and CR Yang 2004;Santana N et al 2009;Gee S et al 2012;Lewis DA et al 2012;Tritsch NX and BL Sabatini 2012;Murray AJ et al 2015;Choi SJ et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…While we did not explore direct MPH induction of DA, others have found it to increase DA release from the PFC, nucleus acumens and caudate-putamen (Carey et al, 1998 ) and also found that it increases frontal cortex and striatal activation (Hellwig-Brida et al, 2011 ). Stress can increase DA release in the PFC (Deutch and Roth, 1990 ; Finlay et al, 1995 ) and elevated D2DR availability in the orbitofrontal cortex has been linked in humans with social anxiety disorder symptoms (Plavén-Sigray et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%